Rabbit Anti-thymocyte Globulin (rATG) as Induction Immunosuppression Therapy in Patients Undergoing Renal Transplantation: Clinical Experience from RISE Registry - Ray, Deepak Shankar; Gang, Sishir; Khullar, Dinesh; Bhalla, Anil Kumar; Sharma, Ashish; Abraham, Abi; Raju, Sree Bhushan; Siddhi, Vishwanath; Dutta, Arup R.; Abraham, Georgie; Shekar, M Soma; Shah, Bharat V.; et al. (Indian journal of transplantation, 2023)
Introduction: Induction immunosuppression therapy plays a significant role in the prevention of acute rejection in renal transplantation. This study aimed to evaluate the effectiveness and safety of rabbit anti-thymocyte globulin (rATG) used as induction immunosuppression in Indian patients undergoing renal transplantation. Patients and Methods: RISE was a multicenter (n = 20), prospective observational cohort study of patients aged ≥ 18 years undergoing a first or repeat renal transplant and receiving rATG as part of the routine management practice. Twelve-month acute rejection was evaluated as a primary endpoint. Results: A total of 325 patients were enrolled, of which 313 patients received at least one dose of rATG with a mean (standard deviation [SD]) duration of induction therapy of 2.07 (1.33) days. The mean (SD) cumulative rATG induction dose was 2.6 (1.5) mg/kg. The mean (SD) glomerular filtration rate was 64.59 (19.57) mL/min/1.73 m2 at 6 months and 64.93 (20.26) mL/min/1.73 m2 at 1 year. The incidence of acute rejection at 1 year was 7.7% (n = 23). Graft rejection at 6 months was observed in 6.7% (n = 20) patients and an average time to first graft rejection of 5.4 and 10.3 months at 6 and 12 months, respectively. In total, 342 adverse events (AEs) were reported (n = 154, 49.2%) after 12 months, of which 11 events were related to the rATG treatment. Pyrexia was the most commonly reported serious adverse event (n = 10, 3.2%). Seven deaths were reported during the study. Conclusions: The study revealed the effectiveness and safety of rATG induction therapy in the Indian context as expected based on the data from randomized clinical trials. Trial Registration Number: CTRI/2017/09/009/009700.